A comprehensive study on the pyrolysis behavior of pine sawdust catalyzed by different metal ions under conventional and microwave heating conditions. (1st June 2023) - Guo, Feiqiang; Qiao, Qixia; Mao, Songbo; Bai, Jiaming; Dong, Kaiming; Shu, Rui; Xu, Liya; Wei, Haixiao; Qian, Lin; Wang, Yunpu
Abstract: The Russia-Ukraine conflict and the COVID-19 pandemic have made fossil energy more urgent, and the catalytic pyrolysis of biomass is conducive to energy transformation to achieve global sustainable development. In this paper, the influence mechanisms of different metal ions on biomass pyrolysis under conventional heating and microwave heating conditions were studied. Through thermogravimetric analysis, it was found that the existence of metal ions could change the pyrolysis behaviors of biomass, leading to different degrees of changes in the main pyrolysis temperature and range. Compared with conventional heating conditions, metal ion-loaded biomass samples exhibited higher heating rates under microwave heating conditions due to the possible hotspot phenomenon, resulting in increased gas yields and decreased bio-oil yields. Among them, the trivalent iron ion exhibited excellent catalytic properties for gas generation, with a high gas yield of 57.9% and a bio-oil yield of 12.1%. The components in bio-oil were greatly simplified by microwave irradiation, the number of the bio-oil compounds from the pyrolysis of Fe-loading pine sawdust was reduced to 77, and the GC-MS area of light compounds with carbon number less than 10 was increased to 84.4%. Phenol and furan in bio-oil are also catalytically converted into aromatic hydrocarbons, which are ideal chemical raw materials. Graphical abstract: Image 1 Highlights: Fe (Ⅲ) promoted the secondary weight loss of biomass at about 666 °C. Metal ions shorten the microwave heating time of biomass to less than 3 min. Gas and syngas yields of the Fe–P samples reached 57.9% and 559.6 mL/g respectively. A composite of biomass porous carbon and metal was obtained. The number of compounds in bio-oil was reduced to 49, 77 and 71 by metal ions.